Minas é o Beco do Mota: a Décima Predial Urbana e as dinâmicas socioespaciais do arraial do Tijuco entre os séculos XVIII e XIX - Letícia Bedendo Campanha Pires (2022)
This research focus on the socio-spatial dynamics of the arraial do Tijuco, current city of Diamantina (MG), starting from the 18th century until becoming a village in 1831. The main source for investigating the urban space is the tax entitled Décima Predial Urbana. Nevertheless, the research makes use of a varied auxiliary set of documents, such as historical cartography and list of names of inhabitants. Together, these documents make possible to correlate the registered properties and the social status of their owners and/or tenants. Therefore, it is possible to identify aspects of the economy and the segregation in the camp, formation of agglomerations and public spaces. In the meantime, the geoprocessing tool is chosen as an instrument for spatializing the data, allowing comparisons between the years collected and the urban tissue. In the end, a methodology for systematizing the information contained in the Décima will be consolidated, as well as for understanding both formal land use practices and private occupation processes that led to the formation of the Diamantina landscape.